Synthesis, diagnosis, and study of the electrical properties of some new iron-polymer complexes containing Schiff bases and study of their thermal stability - Abduljaleel Muhammad Abduljaleel; Nadia Ashour Hussein; Jassim Mohammed Saleh ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Three compounds of the type Schiff bases were prepared from previously prepared and characterized compounds. They were characterized by infrared spectroscopy and nuclear magnetic resonance spectroscopy and reacted with terephthalic chloride to prepare new polyamides. Then three iron complexes were prepared and these polymers and their complexes were characterized by infrared spectroscopy and TGA measurements. Studies of the solid-state electrical conductivity of these polymers and their complexes have shown that they are capable  of partial electrical conduction, which allows them to be used as semi-conducting materials.